Acidizing corrosion inhibitors: A review - Singha A.; Quraishi M.A. (My University, 2025)
Oil well are periodically acidized for enhancing oil flow. Inhibited hydrochloric acid is used during acidization to prevent corrosion of N80 or J55 steel. In the present work authors have surveyed literature on acidizing corrosion inhibitors and the salient features of research work carried out by the authors have also been highlighted.